2006
DOI: 10.1007/s11055-006-0049-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal organization of the reticular nucleus of the thalamus in adult humans

Abstract: The neuronal composition of the thalamic reticular nucleus was studied in serial sections of the sagittal and frontal projections impregnated with silver nitrate by the Golgi method. The neuronal composition of the reticular nucleus of the human thalamus was wider than has previously been described in animals and humans. This nucleus, apart from two types of large, sparsely branched, long-dendrite, reticular, aspiny, neurons, i.e., types R1 and R2, contained cells with spines. Intermediate and small, sparsely-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…At the spacious rostral pole of TRN, neurons have round perikarya and multipolar dendrites. In the cramped central-posterior TRN sectors neurons have elongated and flattened perikarya and sparsely branched dendrites (Nakatani, 1993; Ulfig et al, 1998; Berezhnaya, 2006). These variations reflect the impact of mechanical factors on the morphology of neurons, as in other brain regions (Feldman and Peters, 1978; Hilgetag and Barbas, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…At the spacious rostral pole of TRN, neurons have round perikarya and multipolar dendrites. In the cramped central-posterior TRN sectors neurons have elongated and flattened perikarya and sparsely branched dendrites (Nakatani, 1993; Ulfig et al, 1998; Berezhnaya, 2006). These variations reflect the impact of mechanical factors on the morphology of neurons, as in other brain regions (Feldman and Peters, 1978; Hilgetag and Barbas, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…B. Scheibel [29] described in the TRN a population of multipolar neurons of various sizes, similar to the ones in the reticular formation in the brainstem. Berezhnaya [5] describes in detail the neuronal organization of the TRN in the human using silver nitrate impregnation by the Golgi method. Using the Ortolux (Leitz, Germany) microscope, in this study the authors investigated and drew all the sections in sagittal and frontal planes.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies on cats report that the dendrites of the TRN neurons form a local inhibitory internal network [13]. Berezhnaya [5] describes in detail the morphology of the TRN neurons, and according to this study when comparing the TRN cells in the human and the other species it can be found that the classical aspiny neurons of types R1 and R2 are indeed identical [21]. Apart from these cells, this study reports that in the human TRN is also found another type of R1 reticular neurons with spinelike processes on their bodies and the proximal parts of their dendrites.…”
Section: Introductionmentioning
confidence: 99%